The wind in the willows - Grahame, Kenneth, 1859-1932.; Morrill, Leslie H. (New York : Bantam Books, 1982)
Recounts the escapades of four animal friends who live along a river in the English countryside--Toad, Mole, Rat, and Badger.
"First published in 1908"--T.p. verso.
Young Adult.
Young Adult
Keywords: Animals -- Fiction; Animals -- Fiction; Fantasy fiction; Fantasy